Hak Kewarganegaraan dan Penguasaan Sumber Daya Agraria: Perspektif Keadilan Sosial - Muhamad Fatih Al Farizy; Ayu Dwi Kusuma Wardani; Uswatun Hasanah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Citizenship rights and control of agrarian resources are two interrelated aspects in realizing social justice in Indonesia. In the context of an agrarian country experiencing pressures from economic globalization and resource liberalization, unequal access to land and other agrarian resources has become a pressing structural issue. This study aims to analyze how citizenship rights—as a form of state recognition of the existence and participation of citizens—correlate with the distribution and control of agrarian resources, particularly within the framework of social justice. The method used is a qualitative approach with literature studies and critical analysis of agrarian policies, citizenship regulations, and case studies of agrarian conflicts in several regions of Indonesia. The results show that the neglect of citizenship rights in agrarian policies contributes to the marginalization of vulnerable groups, such as indigenous communities and small farmers. Furthermore, land tenure policies that tend to favor corporations reinforce structural inequality. In conclusion, social justice in the control of agrarian resources requires the integration of substantive recognition of citizenship rights and agrarian reform oriented towards redistribution and participation. Policy reform that guarantees equal access to resources for all citizens is a primary prerequisite for inclusive and equitable development.